Temperature Performance Analysis of a Photovoltaic Module: - Onyenweuwa, A. H. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2019)
The electrical efficiency of photovoltaic (PV) cell is affected by significant increase of cell operating temperature. The efficiency and temperature performance variation on two mono-crystalline modules with and without an active cooling system have been studied. Experimental investigation performed on both modules at different period of the day, under the same ambient temperature reveals that the module efficiency is affected by substantial changes in cell temperature. The module efficiency increases and decreases as temperature decreases and increases respectively. The minimum and maximum module temperatures recorded are 21°C and 102°C while the minimum and maximum module efficiencies are 15.27% and 9.80% respectively. The efficiency performance of the cooled module was high compared with the uncooled module and this indicates that the reduction in cell temperature due to active cooling process improved the efficiency of the module